2010
DOI: 10.1002/chem.201001856
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive, Label‐Free, Aptamer‐Based Biosensor Using a Gold Nanoparticle‐Initiated Chemiluminescence System

Abstract: We report a label-free, aptamer-based chemiluminescent biosensor. The biosensor relies upon the catalytic activity of unmodified gold nanoparticles (AuNPs) on the luminol-H(2)O(2) chemiluminescence (CL) reaction, and the interaction of unmodified AuNPs with the aptamer. The unmodified AuNPs can effectively differentiate unstructured and folded aptamer. The binding of the aptamer with the target can induce the AuNP aggregation in the presence of 0.5 M NaCl, and after aggregation the catalytic activity of the Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…90 Qi reported a label-free, aptamer-based chemiluminescence system based on aptamer-conjugated gold nanoparticles (AC-AuNPs) and the catalytic activity of unmodified AuNPs on the luminol–H 2 O 2 reaction. 91 When the aptamer binds to its target, it induces aggregation of AuNPs and enhances the luminol–H 2 O 2 chemiluminescence reaction (Figure 11). The results proved to be almost 4 orders of magnitude more sensitive than the current AuNPs-based colorimetric method, as thrombin was detected at a concentration as low as 26 fM.…”
Section: Aptamer-based Cell Capture and Detectionmentioning
confidence: 99%
“…90 Qi reported a label-free, aptamer-based chemiluminescence system based on aptamer-conjugated gold nanoparticles (AC-AuNPs) and the catalytic activity of unmodified AuNPs on the luminol–H 2 O 2 reaction. 91 When the aptamer binds to its target, it induces aggregation of AuNPs and enhances the luminol–H 2 O 2 chemiluminescence reaction (Figure 11). The results proved to be almost 4 orders of magnitude more sensitive than the current AuNPs-based colorimetric method, as thrombin was detected at a concentration as low as 26 fM.…”
Section: Aptamer-based Cell Capture and Detectionmentioning
confidence: 99%
“…There are many reports on the aptamer based biosensors for detection of various proteins including lysozymes (Li et al, 2010a, thrombin (Li et al, 2010b;Qiu et al, 2010;Qi and Li, 2011), Creactive protein (Qureshi et al, 2010) and antibodies (Ohno et al, 2010) etc. Recently, mycotoxin (specifically OTA) detection using aptasensor has gained much attention (Cruz-Aguado and Penner, 2008b;Barthelmebs et al, 2011;Sheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect was observed for luminol-H 2 O 2 - Cit-AuNPs. Based on previous reports414445464748 we suggested that the enhancement effect of low concentrations of Cys on luminol–AgNO 3 -AuNPs reaction may be due to the change of the gold nanoparticles surface-charge density. It is obvious that the negative charge density of AuNPs surface decreases after aggregation which occurs in the presence of Cys.…”
Section: Resultsmentioning
confidence: 64%